A Novel Optimal Robust Design Method for Frequency Regulation of Three-Area Hybrid Power System Utilizing Honey Badger Algorithm. (15th November 2022) - Khadanga, Rajendra Kumar; Nayak, Smruti Ranjan; Panda, Sidhartha; Das, Deepa; Prusty, B. Rajanarayan; Sahu, Preeti Ranjan
Abstract : This study proposes an innovative technique for the load frequency control (LFC) of a three-area hybrid power system by putting into consideration of honey badger algorithm-based fractional order proportional integral derivative (FOPID) controller. The algorithm's veritable use is attempted by arranging a FOPID controller for the hybrid system's frequency regulation; the incredible potential of the proposed algorithm is proven. The proposed HBA-based FOPID regulator is presented by comparing its results with other current methods. It is seen that the said regulator is more viable for the frequency control contrasted with the regular regulator by considering a change in system parameters and different paces of RES penetration. It is also seen that the recommended controller is found to be more effective for load frequency control than the conventional controllers.